Pengembangan LKPD untuk Meningkatkan Literasi Sains Peserta Didik Sekolah Dasar - Fitri Handayani; Narhendi; Pramudiyanti; Pramita Sylvia Dewi (STKIP PGRI Bandar Lampung, 2024)
The use of Student Worksheets (LKPD) based on Discovery Learning is an interesting approach in an effort to increase students' scientific literacy. This research aims to explore the effectiveness of Discovery Learning-based LKPD in increasing students' scientific literacy. This research uses the ADDIE research model with research subjects totaling 30 students in class IV UPTD SDN 23 Negeri Katon. This development research has produced Student Worksheets (LKPD) which have been tested through validation and evaluation, and declared